What do people make of “Ecosystem Based Fisheries Management”? - Briguglio, Marie; Ramírez-Monsalve, Paulina; Abela, Glenn; Armelloni, Enrico Nicola (Frontiers in Marine Science, 2025)
The topic of Ecosystem Based Fisheries Management (EBFM) and related terminology has attracted considerable scholarly debate and inspired regulatory interventions across Europe. Yet little attention has been paid to the general public’s awareness or understanding of this term and its implications for marine policy. We employ a unique and representative data set (n=542) from the United Kingdom (UK) and examine (i) the extent to which the public is aware of the concept of Ecosystem Based Fisheries Management, (ii) the demographic correlates of such awareness and understanding, and (iii) whether the public’s understanding converges with scientific notions and regulatory definitions. Our headline finding is that the vast majority of adults in the UK have never heard of EBFM. Participants who attempt to explain what they understood by EBFM associate it primarily with protecting the marine environment and safeguarding fish stocks. While this broadly conforms to scientific and regulatory notions, very few respondents mention socio-economic aspects, regulatory considerations, reliance on science/data or climatic issues. Examination of the correlates of awareness reveals that people who work in marine sectors, who fish more regularly, who have higher awareness of sustainability issues, and who are financially better off are more likely to have heard of EBFM. Among those who attempted a definition, older people were more likely to mention maintaining fish stocks, and people with higher marine education or whose family members worked in the marine sector, were more likely to mention regulatory aspects. Data and climate themes were less likely to be mentioned by those who had never heard of EBFM. Public support can be pivotal for successful implementation of fisheries management, but our findings suggest that there remains a significant gap to be addressed between scientific/regulatory notions and the public’s understanding of EBFM. In this regard, we offer some insights for communication of EBFM among the UK public.